Synthesis, characterization and in vitro cytotoxicity of the first palladium(II) oxalato complexes involving adenine-based ligands - Starha, Pavel; Trávnícek, Zdenek; Popa, Igor (Journal of inorganic biochemistry, 2009)
The first [Pd(L(n))(2)(ox)] xH(2)O oxalato(ox) complexes involving 2-chloro-N6-(benzyl)-9-isopropyladenine (L(1); complex 1), 2-chloro-N6-(4-methoxybenzyl)-9-isopropyladenine (L(2); 2), 2-chloro-N6-(2,3-dimethoxybenzyl)-9-isopropyladenine (L(3); 3), 2-chloro-N6-(2,4-dimethoxybenzyl)-9-isopropyladenine (L(4); 4), and 2-chloro-N6-(4-methylbenzyl)-9-isopropyladenine (L(5); 5) have been synthesized by the reactions of potassium bis(oxalato)palladate(II) dihydrate, [K(2)Pd(ox)(2)].2H(2)O, with the mentioned organic compounds (H(2)ox=oxalic acid; x=0 for 1-3 and 5 or 2 for 4). Elemental analyses (C, H, N), FTIR, Raman and NMR ((1)H, (13)C, (15)N) spectroscopies, conductivity measurements and thermal studies (thermogravimetric and differential thermal analyses, TG/DTA) have been used to characterize the prepared complexes. The molecular structures of [Pd(L(2))(2)(ox)] (2) and [Pd(L(5))(2)(ox)].L(5).Me(2)CO (5.L(5).Me(2)CO) have been determined by a single crystal X-ray analysis. The geometry of these complexes is slightly distorted square-planar with two appropriate L(n) (n=2 or 5) molecules mutually arranged in the head-to-head (2) or head-to-tail (5) orientation. The L(n) ligands are coordinated to the central Pd(II) ion via the N7 atoms. The same conclusions regarding the binding properties of L(1)-L(5) ligands can be made based on multinuclear NMR spectra. In vitro cytotoxicity of the complexes 1-5 has been evaluated against human chronic myelogenous leukaemia (K562) and human breast adenocarcinoma (MCF7) cancer cell lines. Significant cytotoxicity has been determined for the complexes 3 (IC(50)=6.2 microM) and 5 (IC(50)=6.8 microM) on the MCF7 cell line, which is even better than that found for the well-known and widely-used platinum-bearing antineoplastic drugs, i.e. oxaliplatin and cisplatin.
Keywords: krystalografie rentgenová; protinádorové látky; ligandy; Cell Line, Tumor; Adenine; molekulární struktura; Molecular Structure; adenin; Ligands; Oxalates; Organometallic Compounds; Crystallography, X-Ray; Palladium; palladium; lidé; Humans; oxaláty; nádorové buněčné linie; Antineoplastic Agents; organokovové sloučeniny